METHODOLOGICAL BASIS FOR EVALUATING THE ACTIVITY OF INFRASTRUCTURES SERVING PRODUCTION INFRASTRUCTURE - Nurali Holmatovich Bekmurodov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article provides a wealth of information on the concept of infrastructure assessment. Based on the goals and objectives of the assessment, it includes consideration of its socio-economic and other indicators. In addition, the opinions of scientists about the efficiency indicators of the infrastructure complex are cited.